Correlation of Vertical Dimensions of Soft Tissue Facial Profiles - Afrah Kh Al-Hamdany; Nagham H Kassab (University of Mosul, College of Dentistry, 2010)
Aims: To establish the interrelationships of linear measurements of the vertical facial heights among dif-ferent facial profiles in young Iraqi adult students. Materials and Methods: 75 students (48 males, 27females) of pleasing face, balanced facial profile were selected from the College of Dentistry, University of Mosul. For each subject seven vertical linear measurements{ Anterior facial height (n-gn), upper facial third, frontal third (tr-n ), middle facial third, nasal third (n-sn), lower facial third, gnathic third, (sn-gn), rest vertical dimension (RVD)(pn-pog), occlusal vertical dimension (OVD) (pn-pog) and angle of soft tissue profile facial convexity excluding the nose (n-sn-pog)} were measured directly on the subject's face under standarized conditions keeping Frankfort plane parallel to floor, using electronic digital vernier cali-per (China). Results: sn-me, n-sn and free way space are significantly larger, while pn-pog (OVD) is sig-nificantly smaller in concave facial profiles (p≤ 0.05) indicating that the lower and middle facial thirds are responsible for the greater anterior facial height in these subjects compared with other facial profiles' sub-jects. The remaining variables distributed on statistical levels of difference between the upper and lower levels with non-significant difference (p>0.05) within facial profiles. Various correlations were noticed among all the studied variables for total sample, males and females and in different facial profiles. Of most important, is the positive significantly high correlation of pn-pog (OVD) and pn-pog (RVD) with n-me, sn-me for convex and straight profiles. Conclusions: From this study ,spatial relationships among various vertical facial dimensions and the dimensional proportions of different facial profiles in young Iraqi adult students were noticed.